(untitled) - Catsberg, C. M. E. (New York, 1990)
The first four chapters give a general introduction and deal with, in this oder, production, distribution and legislation, (chapter1), potential forms of quality deterioration and spoilage,..
Keywords: Food industry and trade,Thương mại và công nghiệp thực phẩm